2020
DOI: 10.14309/crj.0000000000000298
|View full text |Cite
|
Sign up to set email alerts
|

Achalasia Revealed by Respiratory Failure and Hemodynamic Instability

Abstract: Achalasia is a rare condition that most often presents with progressive dysphagia to solids and liquids. We report a case of achalasia presenting with acute respiratory failure and hemodynamic instability requiring both ventilator and vasopressor support because of extrinsic compression of the airway and left atrium by a dilated and fluid-filled esophagus. This is the first case reported of achalasia, causing both left atrial compression and airway compression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In achalasia, the likely mechanism of elevated troponins is postulated to be left atrial compression secondary to the enlarged esophagus resulting in myocardial damage and cTn release. Left atrial compression secondary to an enlarged esophagus is rare and reported to present as heart failure and hemodynamic instability and with symptoms of ACS without troponin elevation [12][13][14][15]. In our case, left atrial compression due to close anatomical proximity of the dilated esophagus and left atrium likely caused cTn release due to an increase in myocardial wall stress causing reduced subendocardial perfusion [16].…”
Section: Discussionmentioning
confidence: 69%
“…In achalasia, the likely mechanism of elevated troponins is postulated to be left atrial compression secondary to the enlarged esophagus resulting in myocardial damage and cTn release. Left atrial compression secondary to an enlarged esophagus is rare and reported to present as heart failure and hemodynamic instability and with symptoms of ACS without troponin elevation [12][13][14][15]. In our case, left atrial compression due to close anatomical proximity of the dilated esophagus and left atrium likely caused cTn release due to an increase in myocardial wall stress causing reduced subendocardial perfusion [16].…”
Section: Discussionmentioning
confidence: 69%